Inhibition of Lateral Prefrontal Cortex Produces Emotionally Biased First Impressions: A Transcranial Magnetic Stimulation and Electroencephalography Study. (July 2017) - Lapate, Regina C.; Samaha, Jason; Rokers, Bas; Hamzah, Hamdi; Postle, Bradley R.; Davidson, Richard J.
Optimal functioning in everyday life requires the ability to override reflexive emotional responses and prevent affective spillover to situations or people unrelated to the source of emotion. In the current study, we investigated whether the lateral prefrontal cortex (lPFC) causally regulates the influence of emotional information on subsequent judgments. We disrupted left lPFC function using transcranial magnetic stimulation (TMS) and recorded electroencephalography (EEG) before and after. Subjects evaluated the likeability of novel neutral faces after a brief exposure to a happy or fearful face. We found that lPFC inhibition biased evaluations of novel faces according to the previously processed emotional expression. Greater frontal EEG alpha power, reflecting increased inhibition by TMS, predicted increased behavioral bias. TMS-induced affective misattribution was long-lasting: Emotionally biased first impressions formed during lPFC inhibition were still detectable outside of the laboratory 3 days later. These findings indicate that lPFC serves an important emotion-regulation function by preventing incidental emotional encoding from automatically biasing subsequent appraisals.